2011
DOI: 10.2298/ntrp1101018d
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of radiation-induced defects in burn-in stressed power VDMOSFETs

Abstract: The annealing of radiation-induced defects in burn-in stressed n-channel power VDMOSFETs with thick gate oxides (100 and 120 nm) is analysed. In comparison with the previous spontaneous recovery, the changes of device electrical parameters observed during annealing are highlighted by the elevated temperature and voltage applied to the gate, and are more pronounced in devices with a 120 nm thick gate oxide. The threshold voltage of VDMOSFETs with a 100 nm thick gate oxide during annealing has an initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The changes in threshold voltage and mobility associated with electrical stressing and post-stress recovery in MOS transistors are known to originate from the complex electrochemical processes, which include the buildup of gate oxide charges and interface traps during the stress, as well as their removal (charge neutralization=annihilation and trap passivation) during the subsequent recovery, especially upon annealing. [7][8][9][10][11][12][15][16][17][18][19] For further analysis in this study, it is thus required to determine the underlying changes in the densities of gate oxide charges (ΔN ot ) and interface traps (ΔN it ). To clarify the mechanisms responsible for the phenomena observed, ΔN ot and ΔN it were determined by single transistor mobility (STM) 7) and subthreshold midgap (SMG) 21) techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in threshold voltage and mobility associated with electrical stressing and post-stress recovery in MOS transistors are known to originate from the complex electrochemical processes, which include the buildup of gate oxide charges and interface traps during the stress, as well as their removal (charge neutralization=annihilation and trap passivation) during the subsequent recovery, especially upon annealing. [7][8][9][10][11][12][15][16][17][18][19] For further analysis in this study, it is thus required to determine the underlying changes in the densities of gate oxide charges (ΔN ot ) and interface traps (ΔN it ). To clarify the mechanisms responsible for the phenomena observed, ΔN ot and ΔN it were determined by single transistor mobility (STM) 7) and subthreshold midgap (SMG) 21) techniques.…”
Section: Resultsmentioning
confidence: 99%
“…However, our research on the electrical stress and radiation effects in power VDMOS transistors, primarily in terms of their electrical parameter degradation, indicated that the application of electrical stress as a technique for radiation hardening could not lead to the expected results. 11,[16][17][18][19] This conclusion was particularly based on the behavior of channel carrier mobility observed during stress, recovery, and irradiation. Namely, the radiation-induced mobility degradation was lower in the stressed devices than in the virgin ones, but the mobility in the stressed devices was significantly reduced by the pre-irradiation electrical stress itself and was only partially restored by recovery treatment, so it remained below those in virgin devices over the entire range of radiation doses applied.…”
Section: Introductionmentioning
confidence: 97%
“…Since the iso la tion ox ide of pnp tran sis tors is very thick (ap prox i mately 500 nm, as al ready men -tioned), a very high con cen tra tion of the ox ide-trapped charge is ex pected, since the in duced build-up of the ox ide-trapped charge is higher in thicker ox ides [24]. How ever, the pos i tive ef fect of trapped charge in the ox ide may be re duced if the lat eral pnp tran sis tor op erates with high-cur rent den sity, pri mar ily due to a reduc tion of the emit ter in jec tion ef fi ciency and the appear ance of emit ter crowd ing ow ing to the small per im e ter-to-area ra tio of the base-emit ter junc tion.…”
Section: Re Sults and Discussionmentioning
confidence: 97%
“…Among the others, in Refs. [17][18][19], the effects induced by previous irradiation and the total dose received strongly affect the subsequent stresses. Specifically, in the case of low-dose irradiation, following stress caused by working in specific applications, this appears to result in device degradation in the future.…”
Section: Introductionmentioning
confidence: 99%